Aplikasi Musik Instrumental Dalam Menurunkan Ansietas Pada Pasien Prioritas 4 di Ruang Unit Gawat Darurat - Imelda Feneranda Tambi; Rufina Hurai; Theresia Tutik Ismiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background: Emergency departments have a busy, noisy environment and can cause anxiety to patients. Patients who come to the emergency room have increased anxiety due to the unfamiliar environment, crowds, and actions that are carried out quickly. The increasing level of anxiety can have an effect on the pain experienced by the patient. Priority 4 patients usually suffer from an acute incident with a stable condition and often have a long waiting time. Management of anxiety and pain in patients is not only done by using medical and invasive therapy. Independent nursing interventions can also be carried out by nurses. Interventions to deal with anxiety in the emergency room are very important. The actions taken should be able to help the patient to adjust to the emergency room environment and the various actions taken. Purpose: Knowing the implementation of music therapy to reduce anxiety in priority 4 patients in the emergency room. Methods: This research method is a quasi-experimental Result: There is an effect of the application of instrumental music in reducing anxiety in priority 4 patients in the emergency room with a significance value of 0.017, and there is a difference between the control and treatment groups with a significance value of 0.006. Conclusion: The Use of Instrumental Music Can Reduce Anxiety in Priority 4 Patients in the Emergency Room Music therapy can be given as an independent intervention by nurses to priority 4 patients in the emergency room. Music therapy can reduce the patient's anxiety level about noise and actions performed in the emergency room